Telemedicine platform COVIDREHAB for remote rehabilitation of patients after COVID-19 - Ilmira R. Gilmutdinova; Vasiliy A. Kolyshenkov; Kristina A. Lapickaya; Anastasiya S. Trepova; Valeriia A. Vasileva; Andrei N. Prosvirnin; Larisa A. Marchenkova; Kirill V. Terentev; Maxim Y. Yakovlev; Andrey P. Rachin; Anatoliy D. Fesyun; Igor V. Reverchuk (PAGEPress Publications, 2021)
The world's practice has shown the importance of medical rehabilitation, which allows increasing the effectiveness of treatment of patients with COVID-19, and also significantly reduce the risks of developing complications after COVID-19. Moreover, timely medical rehabilitation reduces the frequency of disability retirement. We developed and investigated the effectiveness of the telemedicine platform "COVIDREHAB" in order to enhance the effectiveness of the recovery period during self-isolation, as well as to provide access to rehabilitation for patients residing in remote areas or unable to undergo in-person medical rehabilitation. This pilot open clinical study includes 178 patients (108 women and 70 men) aged 32 to 82 years [mean age 50 (33-56) years] who had a moderate disease of COVID-19. We used the specialised platform COVIDREHAB for remote monitoring of the rehabilitation efficiency of patients who suffered from COVID-19. During the study, the supervising doctor assigned the patient a set of specialised questionnaires, which were filled in online. The questionnaires distributed to the patient included questions specifically designed for the COVIDREHAB remote platform as well as the mMRC (Modified Medical Research Council) questionnaire. Patients who completed the remote rehabilitation programme were found to have positive dynamics of indicators of the respiratory system functional state, and complaints.Pulmonary rehabilitation is an important part of case management for patients with respiratory diseases and plays an active role in improving lung function and general well-being of patients. Patients who completed the comprehensive medical rehabilitation program using the information and analytical system COVIDREHAB, were found to have positive dynamics of indicators of the respiratory system functional state, and complaints. Hence, at the end of the course the shortness of breath severity decreased (from 34.8% to 12.4%, as well as the feeling of lack of oxygen from 32% to 17.4%, p <0.05). We anticipate the online approach to rehabilitation will improve the functioning of the respiratory and cardiovascular systems, restore physical function, reduce anxiety and depression, and restore quality of life. An essential benefit of this program is the prevention of secondary complications and reduction of serious adverse effects of COVID-19 treatment."